The Correlation Between Knowledge and Attitude About Covid-19 with Compliance with the use of Masks at Masombamarket - Nur Afni; Nurhidaya Nurhidaya; Nurjanah Nurjanah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Non-compliance with the application of health protocols can expand the spread of COVID-19, particularly in public places such as markets. In preoobservations at Masomba market, a small number had used masks properly, but some wore marks on their necks, and many of them did not use masks when trading. The purpose of this research is to determine the correlation between knowledge and attitude about COVID-19 with compliance with the use of masks at the Masomba market. This is quantitative research with a cross-sectional approach using the Chi-Square test and an alpha value = 0,05. The sample of this research is 83 respondents. The independent variables are knowledge and attitudes, and the dependent variable is compliance with the use of masks. The results of this research indicate that the value (p-value) = 0,003 ≤ 0,05 then Ho is rejected, which means that there is a correlation between knowledge of COVID-19 and compliance to the use of masks and the p-value = 0,019 ≤ 0,05 then Ho is rejected which means there is a correlation between attitude and compliance with the use of masks. Good knowledge and attitude of traders about COVID-19 can reduce the risk of COVID-19 transmission, which is supported by disciplined health protocols, especially obedience to using masks in public places, and if there are traders who do not comply with mask use, they can be given a warning both verbally and in writing and appropriate sanctions.